Over than three-year follow-up results of thermal ablation for papillary thyroid carcinoma: A systematic review and meta-analysis - Xue, JiaNan; Teng, DengKe; Wang, Hui (Frontiers in Endocrinology, 2022)
Background: This study carried out a meta-analysis based on evidence-based medicine to explore the long-term efficacy (≥ 3 years) of thermal ablation in the treatment of papillary thyroid carcinoma (PTC). Methods: We searched the PubMed, Embase, and Cochrane Library databases for studies published during the time between the establishment of the database through June 2022. We included a 13 non-randomized controlled trial (non-RCT) that reported the application of US-guided thermal ablation in PTC.We excluded repeated publication, researches without full text, incomplete information or inability to conduct data extraction and animal experiments, reviews and systematic reviews. STATA 15.1 software was used to analyze the data. Results: The tumor volume after thermal ablation at 3-years follow-up was significantly lower than pre-ablation ((Standardized mean difference (SMD) = -1.06, 95%CI: -1.32~ -0.80). The pooled results showed that VRR after thermal ablation at 3-years follow-up was 98.91% (95%CI: 97.98-99.83%), and the pooled results showed that CDR after thermal ablation at 3-years follow-up was 83% (95%CI: 67-94%). Additionally, pooled results showed the incidence of newly discovered mPTC and lymph node metastases after thermal ablation were respectively 0.3% (95%CI: 0.0-1.0%) and 0.0% (95%CI: 0.0-0.0%). Conclusion: Overall, the long-term efficacy (3 years) of ultrasound-guided thermal ablation in the treatment of PTC was significant with good disease progression. It can be considered an alternative approach for patients with PTC who refuse surgery or are unable to undergo surgery.